2016
DOI: 10.1021/acsami.6b00207
|View full text |Cite
|
Sign up to set email alerts
|

Unique Core–Shell Nanorod Arrays with Polyaniline Deposited into Mesoporous NiCo2O4 Support for High-Performance Supercapacitor Electrodes

Abstract: Polyaniline (PANI), one of the most attractive conducting polymers for supercapacitors, demonstrates a great potential as high performance pseudocapacitor materials. However, the poor cycle life owing to structural instability remains as the major hurdle for its practical application; hence, making the structure-to-performance design on the PANI-based supercapacitors is highly desirable. In this work, unique core-shell NiCo2O4@PANI nanorod arrays (NRAs) are rationally designed and employed as the electrode mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(90 citation statements)
references
References 40 publications
(53 reference statements)
3
87
0
Order By: Relevance
“…A Pt plate is used as the counter electrode, and an Hg/HgO is used as the reference electrode. [44][45][46] From the CV curves of CC@ NiCo 2 O 4 , the peak positions only shift a little when the scan rate increased from 5 to 100 mV s −1 , indicating that the electrode has very good reversibility. For comparison, the solid Co 3 O 4 nanowalls on carbon cloth (noted as CC@Co 3 O 4 ) obtained by directly annealing the Co-MOF precursor in air is also tested, and detailed characterization of the solid Co 3 O 4 nanowalls can be found in Figure S3 (Supporting information).…”
Section: Supercapacitive Propertymentioning
confidence: 99%
“…A Pt plate is used as the counter electrode, and an Hg/HgO is used as the reference electrode. [44][45][46] From the CV curves of CC@ NiCo 2 O 4 , the peak positions only shift a little when the scan rate increased from 5 to 100 mV s −1 , indicating that the electrode has very good reversibility. For comparison, the solid Co 3 O 4 nanowalls on carbon cloth (noted as CC@Co 3 O 4 ) obtained by directly annealing the Co-MOF precursor in air is also tested, and detailed characterization of the solid Co 3 O 4 nanowalls can be found in Figure S3 (Supporting information).…”
Section: Supercapacitive Propertymentioning
confidence: 99%
“…Transition metal oxides have several advantages over other pseudocapacitive materials owning the properties of low toxicity, low cost, and natural abundance [11]. Among these transition metal oxides studied so far, ternary metal oxides, like NiCo 2 O 4 [12], CuCo 2 O 4 [13], NiMoO 4 [14], CoMoO 4 [15], and so on, can provide much higher electrical conductivity and richer electrochemical active sites than their single components, and they have been widely studied in the electrochemical energy field [1215]. Although great progress has been made on ternary metal oxides electrodes to improve their electrochemical performance, these electrode materials still suffer from insufficient conductivity, slow ion diffusion rates, and serious volume change during the electrochemical procedure, which limit their further application for improving the performance of supercapacitors [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Potential‐induced phase changes in an electroactive material can be connected with several factors: a cracking of a material can lead to a dramatic rise in the electrode resistance and a rapid loss in the cycling stability . Moreover, the electrical conductivity of PANI becomes lower at a reduced state, which causes large electrode polarization and poor rate capability . To determine the resistivity of the PANI film (the reciprocal of conductivity), we performed electrochemical impedance spectroscopy measurements under various constant potentials: from 0 to 0.7 V, and the results are presented in Figure S5 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the poor mechanical stability of PANI during electrochemical processes, 3D PANI networks (semiconducting polymer gels) have been prepared . Additionally, to improve the mechanical stability and performance of polyaniline, the polymer was deposited as a thin layer on top of a NiCo 2 O 4 /carbon cloth substrate, and it was demonstrated that in such a case, the overall morphology of polyaniline did not change, even after 500 repeated cycles . Polypyrrole, another member of the semiconducting polymer family, combined with cellulose similarly exhibited excellent cycling stability with no changes in the morphology of the electrode material after 4000 galvanostatic cycles …”
Section: Introductionmentioning
confidence: 99%